PERFORMATIF GENDER DAN ALGORITMA: NETNOGRAFI BEAUTY INFLUENCER PRIA INDONESIA DI INSTAGRAM - Putra, Pandika Adi; Puspitasari, Dwi Rina; Farisi, Rizki (Konvergensi, 2025)
The rise of visual-based social media platforms like Instagram has transformed gender representation in the beauty industry, allowing men to emerge as cultural actors who express non-conventional identities. This study aims to analyze how male beauty influencers in Indonesia construct and perform gender in algorithm-driven digital spaces. Using a netnographic approach, the study focuses on the Instagram account @azkhategar, observing visual content, caption narratives, distribution strategies, and audience interaction from March to July 2025. Theoretical frameworks include gender performativity (Butler), hegemonic masculinity (Connell), algorithmic visibility (Cotter), and micro-celebrity (Abidin). Findings reveal that Azka’s gender representation is fluid, performative, and constructed through consistent visual aesthetics aligned with algorithmic logic. Reflective and inclusive narratives in captions function as strategic communication to challenge dominant masculine norms while enhancing audience engagement. Public responses show ambivalence, ranging from affirmative support to conservative resistance, indicating that digital spaces remain contested arenas of gender discourse. Furthermore, Azka’s visibility is highly influenced by Instagram’s algorithm, which privileges engagement and mainstream aesthetics. Thus, gender performance on social media is not merely personal expression but also a commodified act shaped by attention economy dynamics. The study concludes that gender representation in digital media results from the negotiation between subjective identity, social norms, and platform design. It underscores the role of social media as a critical cultural space for articulating and transforming inclusive social identities in the age of algorithms.